Sistema de emisión electrónica de comprobantes de pago y su relación con la evasión tributaria en los restaurantes de los distritos Chaupimarca y Yanacancha, Pasco (2022) - Bernaldo Faustino, Carlos (2022)
The objective of the present investigation was to determine the relationship of the study variables. A correlational design was used. There was a population of 229 restaurants, a sample of 141 of which 57 were from the Chaupimarca district and 84 from Yanacancha. A survey and a questionnaire were used. According to the results, 65.25% of those surveyed use the electronic taxpayer system (SC), 65.25% issue invoices, sales receipts, credit and debit notes electronically and 63.83% use the operator system of electronic services (OSE), 68.09% normally issue invoices, sales receipts, credit and debit notes with the issuance system of electronic billing receipts (FS). Finally, it was concluded that the electronic issuance system of payment vouchers affects tax evasion in restaurants in the Chaupimarca and Yanacancha districts.